Chiropterans as a potential hosts of Leishmania spp. in endemic areas for leishmaniasis in northeastern Brazil. (26th August 2022) - Ramos, Luis Gustavo Siqueira Matias; Costa, Valéria Almeida; Louzeiro, Nayara Mendes; Carvalho, Clauberth César Alves; de Maria Seabra Nogueira, Rita; Speranca, Marcia Aparecida; Cabral, Aline Diniz; Costa, Francisco Borges; Barros, Maria Claudene; da Costa Fraga, Elmary; Marcili, Arlei; da Costa, Andréa Pereira
Abstract: The species of the genus Leishmania are protozoa that are widely distributed from Asia to the Americas, affecting humans and wild and domestic animals. Little is known about infection by Leishmania in bats in the state of Maranhão, Brazil. The objective of this study was to investigate the presence of Leishmania in bats in Maranhão. Blood samples were collected from bat species for parasitological diagnosis. Samples of spleen and liver were collected for molecular analysis. All the blood cultures were negative. In two blood smears, organisms similar to amastigotes of Leishmania sp. were detected. Of the 116 samples, two spleen samples were positive and showed similarity to Leishmania infantum . Therefore, further studies are needed to elucidate whether bats take part in the epidemiological chain of leishmaniasis.